Passive Immunotherapy: Assessment of Convalescent Serum Against Ebola Virus Makona Infection in Nonhuman Primates - Mire, Chad E. (J Infect Dis, 2016)
Background. Convalescent serum and blood were used to treat patients during outbreaks of Zaire ebolavirus (ZEBOV) infection in 1976 and 1995, with inconclusive results. During the recent 2013–2016 West African epidemic, serum/plasma from survivors of ZEBOV infection was used to treat patients in the affected countries and several repatriated patients. The effectiveness of this strategy remains unknown. Methods. Nine rhesus monkeys were experimentally infected with ZEBOV-Makona. Beginning on day 3 after exposure (at the onset of viremia), 4 animals were treated with homologous ZEBOV-Makona convalescent macaque sera, 3 animals were treated in parallel with heterologous Sudan ebolavirus (SEBOV) convalescent macaque sera, and 2 animals served as positive controls and were not treated. Surviving animals received additional treatments on days 6 and 9. Results. Both untreated control animals died on postinfection day 9. All 4 ZEBOV-Makona–infected macaques treated with homologous ZEBOV-Makona convalescent sera died on days 8–9. One macaque treated with heterologous SEBOV convalescent sera survived, while the other animals treated with the heterologous SEBOV sera died on days 7 and 9. Conclusions. The findings suggest that convalescent sera alone is not sufficient for providing 100% protection against lethal ZEBOV infection when administered at the onset of viremia.